Public Health Policy and its Incidence on The Quality of Public Management in Chincha – Peru, 2021 - Nuñez, Freddy Jhonny Sachun; Gutierrez, Etheel Romila Becerra; Cabrejos, Ruth Gissela Perez; Becerra, Percy Alexander Sachun (South Eastern European Journal of Public Health, 2024)
The objective of this research is to determine how public health policy affects the quality of public management in Chincha 2021. The link between new management and quality is demonstrated by the experience of administrative reform carried out by Latin American governments during the two decades. The countries due to Covid-19 2020 - 2021, had to review current policies, adapt or create new public policies. The research had a quantitative approach, basic type, with a non-experimental cross-sectional design, the hypothetical-deductive method and descriptive causal correlation, using non-probabilistic sampling techniques such as questionnaires. The result is that according to the Nagelkerke indicator, he estimates it at 48.1% (moderate correlation). the estimation of parameters by the Wald=786,021 and following=0.000 method is less than 0.05, concluding that: public health policy significantly affects the quality of public management in Peru 2021.